The given function : h(x) = 6 - x
We know that for any functions f(x) and g(x)
f*g (x)=f(x)\times g(x)
Therefore , h*h (x)=h(x)\times h(x)
h*h (x)=(6-x)(6-x)=(6-x)^2
h*h (x)=(6)^2-2(6)(x)+x^2 [ Using identity (a-b)^2=a^2+2ab+b^2 ]
h*h (x)=36-12(x)+x^2
\-------->\ h*h (x)=36-12(x)+x^2 Now, at x= 10 , we get
h*h (10)=36-12(10)+(10)^2
h*h (10)=36-120+100=36+100-120=136-120=16
Hence, the value of (h*h)(10) = 16
hoped it helped
Answer:
2,700 sq yds :)))) (d)
Step-by-step explanation:
2(30)=60
1.5(30) =45
60(45)= 2700
Answer:
-32+y+90
y=122
Step-by-step explanation:
Sorry I can't solve it.
Firstly, the equation is wrong. It is supposed to be <span>81 ≠ </span><span>30.25
Second of all, this is the best I got </span>81= <span><span>−<span>76 <span>(<span>cos<span>(r) </span></span></span></span></span>+ <span>106.25</span></span>
Answer:
It allows to to know y-intercept formula which is used to graph a line.
Step-by-step explanation:
Y-intercept formula:
y=mx+b
M: slope (keep in fraction if it is fraction, to help you graph)
B: y-interecept